Metabolites From the Mangrove-Derived Fungus Cladosporium sp. HNWSW-1 - Cao, Xi; Guo, Lei; Cai, Caihong; Kong, Fandong; Yuan, Jingzhe; Gai, Cuijuan; Dai, Haofu; Wang, Pei; Mei, Wenli (Frontiers in Chemistry, 2021)
Two new benzoic acids, cladoslide A (1) and cladoslide B (2), one new carboline derivative, cladospomine (3), and one new pyridin-2(1H)-one, cladoslide C (4), were isolated from the fermentation cultures of the mangrove-derived fungus Cladosporium sp. HNWSW-1, along with the previously reported N-acetyl-β-oxotryptamine (5), (4S,5S,11R)-iso-cladospolide B (6), (4S,5S,11S)-iso-cladospolide B (7), and (4R,5S,11R)-iso-cladospolide B (8). Their structures were elucidated by spectroscopic analysis, Rh2(OCOCF3)4-induced ECD experiments, and Marfey’s method. Compound 1 showed cytotoxicity against the K562 cell line with IC50 values of 13.10 μM. Moreover, compound 1 and 5 exhibited inhibitory activity against α-glycosidase with IC50 values of 0.32 mM and 0.17 mM, respectively.